Maneuverability analysis of thrust vectoring ducted propeller with deflector. (1st October 2020) - Xia, Hui; Wang, Peng; Jin, Zhihui; An, Xiaoyi; Ding, Yongle
Abstract: A thrust vectoring ducted propeller with deflector is a new method for vector propulsion that produces lateral forces and torques and manipulates the autonomous underwater vehicle (AUV) for various movements. In this work, the geometric model of the thrust vectoring ducted propeller is designed. The six degree of freedom (DOF) kinematic and dynamic model of a cylinder-shaped AUV equipped with the thrust vectoring ducted propeller is developed based on Newton's equation and Euler's equation considering the forces and torques generated by the ducted propeller with deflector. The performance of the ducted propeller is evaluated using Computational Fluid Dynamic (CFD) method. The simulation of pitch motions, yaw motions, pitch and yaw coupled three-dimensional motions and maneuverability analysis are carried out based on the kinematic and dynamic model. The simulation results demonstrate that thrust vectoring ducted propeller with deflector can achieve accurate control on depth, pitch and yaw angle, and has good maneuverability on three-dimensional motion control. Highlights: A thrust vectoring ducted propeller with deflector is presented. The kinematic and dynamic model of a cylinder-shaped AUV equipped with the thrust vectoring ducted propeller is developed. Lateral forces and torques are generated due to the deflection of the propeller outflow, which is used as control force. The data of trajectory shows good maneuverability of the proposed thrust vectoring ducted propeller with deflector.